2018
DOI: 10.1124/jpet.118.248039
|View full text |Cite
|
Sign up to set email alerts
|

TAS-303, a Novel Selective Norepinephrine Reuptake Inhibitor that Increases Urethral Pressure in Rats, Indicating Its Potential as a Therapeutic Agent for Stress Urinary Incontinence

Abstract: Stress urinary incontinence (SUI) is characterized by involuntary leakage associated with exertion, effort, sneezing, coughing, or lifting. Duloxetine, a serotonin norepinephrine reuptake inhibitor, is approved for the treatment of patients with SUI in some European countries, but not in the United States. There is currently no globally approved pharmacological drug for the treatment of patients with SUI. Therefore, a new pharmacological treatment option is required. TAS-303 [4-piperidinyl 2,2-diphenyl-2-(prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…This condition considerably compromises the quality of life for many women . TAS‐303 (4‐piperidinyl 2,2‐diphenyl‐2‐ [propoxy‐1,1,2,2,3,3,3‐ d 7 ] acetate hydrochloride; Supplemental Figure S1) is a selective noradrenaline reuptake inhibitor that is being investigated as a novel therapy for SUI . In nonclinical studies, TAS‐303 had a time‐dependent inhibitory effect on cytochrome P450 (CYP) 3A, half‐maximal inactivation (K I , 1024 ng/mL), and a maximal inactivation rate constant (K inact , 4.68 h −1 ); unpublished data.…”
mentioning
confidence: 99%
“…This condition considerably compromises the quality of life for many women . TAS‐303 (4‐piperidinyl 2,2‐diphenyl‐2‐ [propoxy‐1,1,2,2,3,3,3‐ d 7 ] acetate hydrochloride; Supplemental Figure S1) is a selective noradrenaline reuptake inhibitor that is being investigated as a novel therapy for SUI . In nonclinical studies, TAS‐303 had a time‐dependent inhibitory effect on cytochrome P450 (CYP) 3A, half‐maximal inactivation (K I , 1024 ng/mL), and a maximal inactivation rate constant (K inact , 4.68 h −1 ); unpublished data.…”
mentioning
confidence: 99%
“…These reports suggest that M3 receptors and β3 adrenoreceptors coordinately regulate the bladder afferents. We previously reported that the concentration of norepinephrine in plasma after TAS-303 administration is elevated in rats (Mizutani et al, 2018). Thus, we hypothesized that norepinephrine elevation due to inhibition of the norepinephrine transporter (NET) may contribute to suppression of bladder afferents via β3 adrenoreceptors.…”
Section: Downloaded Frommentioning
confidence: 97%
“…TAS-303 hydrochloride was synthesized by Taiho Pharmaceutical Co. Ltd. The chemical structure and pharmacological properties of TAS-303 were previously described (Mizutani et al, 2018). Atropine sulfate salt monohydrate, carbamoylcholine chloride (carbachol), and nisoxetine hydrochloride were purchased from Sigma-Aldrich Japan K.K.…”
Section: Chemicalsmentioning
confidence: 99%
See 2 more Smart Citations